Application of microorganisms to determine the impact of infiltration layer and season on pit latrine groundwater contamination - Frank Awuah (Sustinere: Journal of Environment and Sustainability, 2024)
This study was necessitated as a result of the frequent cases of diarrhoea observed among the students of the researcher. The researcher employed faecal indicator bacteria to assess the impact of the infiltration layer and seasonal variations on groundwater contamination from pit latrines in the municipalities where the students reside. The main experimental materials consisted of water samples collected from 15 randomly selected wells in the Tano Districts of Ghana. Total coliforms, faecal coliforms, and enterococci were used as faecal indicators. The Most Probable Number (MPN) method was employed to determine the presence of faecal indicators in the water samples. The results showed that enterococci and faecal coliforms were reliable indicators of human faecal contamination than total coliforms. The study revealed that coliform level (indicating pit latrine groundwater contamination) increased with greater pit depth and lower static water levels. Based on these findings, it is recommended that the future studies on human faecal contamination prioritize enterococci and faecal coliforms over total coliforms as indicators. To mitigate groundwater contamination from pit latrines, the equation EC = 0.12(PLD) – 0.09(SWL) + 2.37 can be applied to predict a safer infiltration layer between the bottom of pit latrines and the water table.